PENGEMBANGAN MODUL PEMBELAJARAN MATA KULIAH ALJABAR LINEAR DENGAN PENDEKATAN INKUIRI TERBIMBING DI STKIP PARIS BARANTAI KOTABARU - Rahmi Yuliana; Hartini Hartini (STKIP Paris Barantai, 2019)
The problem in this study is that the students of STKIP Paris Barantai still have difficulty in understanding the material and sample problems because the learning resources in the form of printed books are less attractive and the language used is difficult to understand, the lecturer has not chosen a learning model that suits the characteristics of students. This study aims to determine the development and feasibility of linear algebra modules with a guided inquiry approach. This research method is Research and Development (R&D) with the model used is 4D. Stages are carried out starting from the definition stage (define), stage of design (design), the stage of development (development) and the stage of deployment (dessemination). The data collected in the form of data about the quality of the product being developed are validity, practicality (attractiveness) and effectiveness. Based on the results of the validation of the material experts obtained an average score of 3.6, the linguists obtained an average score of 4 and the media experts obtained an average score of 3.7 so the developed product was declared valid for use. After validating the product to an expert, the product is then tested on students. Student responses are used to determine the feasibility of the product by obtaining an average score of 3.4 very interesting criteria and also the results of the average student test are in the high category which indicates that student understanding tends to be high and the effectiveness criteria are met. Keywords: Learning Module, Linear Algebra, Guided Inquiry.